2013
DOI: 10.1007/s13277-013-0889-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between vitamin D receptor gene FokI and BsmI polymorphisms and prostate cancer risk: an updated meta-analysis involving 21,756 subjects

Abstract: The vitamin D receptor (VDR) is a crucial mediator for the cellular effects of vitamin D. The polymorphisms in the VDR gene have been hypothesized to alter the risk of prostate cancer. However, studies investigating the association between VDR polymorphisms (BsmI and FokI) and prostate cancer (PCa) risk report conflicting results , therefore, we conducted a meta-analysis to re-examine the controversy. Published literatures from PubMed, Embase, Google Scholar, and China National Knowledge Infrastructure (CNKI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
3
19
0
1
Order By: Relevance
“…A recent meta-analysis, including thirty-four studies for a total of 10,267 cases and 11,489 controls, focused on the association between vitamin D receptor (VDR) polymorphisms, which mediate the cellular effects of vitamin D and risk of prostate cancer. No evidence to support an association between any of the VDR polymorphisms and risk of prostate cancer was found [83]. Further studies have found there to be no convincing association and random control trials are lacking.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis, including thirty-four studies for a total of 10,267 cases and 11,489 controls, focused on the association between vitamin D receptor (VDR) polymorphisms, which mediate the cellular effects of vitamin D and risk of prostate cancer. No evidence to support an association between any of the VDR polymorphisms and risk of prostate cancer was found [83]. Further studies have found there to be no convincing association and random control trials are lacking.…”
Section: Resultsmentioning
confidence: 99%
“…) and cancer risk with inconclusive results (179,238,270,516) (227). Recently, Narvaez et al (323) reported that in The Cancer Genome Atlas datasets Ͻ2% of breast cancers exhibit genomic alterations (including amplifications, deletions, mutations, and changes in mRNA) (323).…”
Section: Vdr Expression and Vitamin D Metabolism In Cancer Cellsmentioning
confidence: 99%
“…However, the results across studies have been equivocal [34, 35, 36]. Previous meta-analyses were performed by Xu et al in 2014, Guo et al in 2013 and Yin et al in 2009 [34, 37, 44]. Xu et al and Yin et al reported the relationship of cancer risk with several VDR SNPs including Fok I .…”
Section: Discussionmentioning
confidence: 99%